2009
DOI: 10.1161/atvbaha.108.173799
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Hit Inhibition of Circulating and Cell-Associated Components of the Toll-Like Receptor 4 Pathway by Oxidized Phospholipids

Abstract: Objective-Oxidized phospholipids (OxPLs) that are abundant in atherosclerotic lesions are increasingly recognized as context-dependent lipid mediators demonstrating both pro-and antiinflammatory activities. Molecular mechanisms of their effects are largely unknown. Here we present novel information on the mechanisms whereby OxPLs modulate activation of TLR4 by lipopolysaccharide (LPS). Methods and Results-We show, using several cell types and various inflammatory genes as readouts, that different classes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 29 publications
10
72
0
Order By: Relevance
“…Previously, we showed that OxPLs inhibited LPS-induced accumulation of both E-selectin mRNA and protein in HUVECs (21). Therefore, only expression of E-selectin mRNA was measured in this work.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Previously, we showed that OxPLs inhibited LPS-induced accumulation of both E-selectin mRNA and protein in HUVECs (21). Therefore, only expression of E-selectin mRNA was measured in this work.…”
Section: Resultsmentioning
confidence: 95%
“…Oxidation was monitored by TLC and electrospray ionization-mass spectrometry (12). Mass-spectra of OxPLs have been published previously (21). 1-Palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphocholine (POVPC), 1-palmitoyl-2-glutaroyl-sn-glycero-3-phosphocholine (PGPC), a mixture of 1-palmitoyl-2-(12-hydroperoxyeicosa-5,8,10,14-tetraenoyl)-sn-glycero-3-phosphocholine and 1-palmitoyl-2-(15-hydroperoxyeicosa-5,8,11,13-tertraenoyl)-sn-glycero-3-phosphocholine (PAPC-OOH), and 1-palmitoyl-2-(5,6-epoxy isoprostane E2)-sn-glycero-3-phosphocholine (PEIPC)-enriched fraction were prepared as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations